An Illustration of Interpersonal Psychotherapy for Perinatal Depression - Tan, Huey Jing Renee (Case Reports in Psychiatry, 2020)
This is a case of a 38-year-old married woman presenting with major depressive disorder one month after the birth of her third child. The depressive episode began in the context of interpersonal difficulties with her husband. In addition, she was also battling an internal conflict of continuing to pursue her career dream as an obstetrician and fulfilling her responsibility as a wife and a mother. Interpersonal psychotherapy (IPT) was selected as the treatment choice as an evidence-based peripartum treatment that could specifically address the two presenting problem areas, i.e., marital interpersonal dispute and role transition. This paper provides an illustration of IPT sessions conducted with verbatim selections of the sessions.